Late Cenozoic glacial history of the Terra Nova Bay Region, northern Victoria Land, Antarctica - OROMBELLI G; DENTON G. H.; BARONI, CARLO (1990)
The Transantarctic Mountains inland of Terra Nova Bay exhibit four major landsapces. 1) The first type consists of deep troughs propagated inland by headward cutting. The lower portions of these troughs form ice-covered fjords, where present-day grounding lines extend inland beneath outlet glaciers. 2) Well-developed alpine glacial topography (with cirques, ridges, horns, and spurs) characterizes the region. Alpine topography has propagated from the deep troughs into the intervening mountain blocks. This morphology can locally be very old and reflects a different-from-present climatic regime. 3) Relict summit mesas occur in the high central mountain ranges between troughs. 4) The fourth type of morphology features undulating coastal piedmonts that are tilted seaward. The process of inland erosion by outlet glacier troughts and adjacent alpine topography has left isolated nearly intact remnants of the original topography. Trimlines superimposed on the alpine and outlet-trough topography mark the maximum possible expansion of the northern Victoria Land ice cover since erosion of the alpine topography. There is no definitive evidence that the East Antarctic Ice Sheet overrode northern Victoria Land nunataks or mountains. High-elevation striations in the Eisenhower Range seem to have been carved during Terra Nova glaciation. If so, local mesa ice caps and mountain glaciers expanded to feed the Terra Nova piedmont glacier during late Wisconsin time, unlike the situation farther south where alpine glacier termini in the Dry Valleys were less extensive than now during late Wisconsin time.